Avaliação pancreática de animais submetidos à dieta hiperlipídica - Pisani, Graziéle Fernanda Deriggi (Universidade Federal de São Carlos, 2012)
The pathogenesis of type 2 diabetes mellitus (DM2) is associated with insulin resistance (IR) and pancreatic β cells (β cells) defect. Adipose tissue modulates metabolism by releasing free fatty acids (FFA), glycerol, pro-inflammatory cytokines, chemokines and hormones. The increased production of most of these factors compromises insulin action in target organs, leading to IR. The lack of β cell adaptation to IR leads to hyperglycemia and DM2. The mechanisms of β cell adaptation are not well established. The objective of the present study was to evaluate the morforlogical and functional patterns of the progression of IR and DM2 development in an animal model of obesity and DM2. Swiss mice were divided into two groups: control (C), received standard diet; HFD group, received high-fat diet. Glucose (GTT) and insulin (ITT) tolerance tests were performed tests at 3, 7, 11 and 15 weeks of diet regimen. Animals of both groups were sacrificed by decaptation at 4, 8 and 16 weeks of diet regimen and pancreatic tissue was analysed. Fasting glycemia and GTT and ITT responses were significantly different in HFD from C group. Immunohistochemical analysis showed that islets area increased and insulin expression decreased in islets of HFD group compared with C group. The expression of the anti-apoptotic factor, Bcl-2, and the concentration of the citokines, TNF-α (factor tumor necrosis factor-α) and IL-1β (interleukin-1β) determinated in pancreatic homogenate by ELISA were not different in the groups. The results indicate that high-fat diet regimen induces pancreatic morphological and functional derangements associated with the development of DM2 in swiss mice. The study also suggests that TNF-α, IL-1β and Bcl-2 are not involved in the pathogenesis of DM2 in this model.
Keywords: Diabetes; Diabetes tipo 2; Camundongos; Pâncreas - doenças; Dieta hiperlipídica; Type 2 Diabetes; High-fat diet; Swiss mice; Pancreas; CIENCIAS BIOLOGICAS::FISIOLOGIA